Trends in Sieving and Its Applications in Cereals. A Literature Review - Sanchez-Suarez, Nevardo; Orozco-Mendoza, Gina Lia; Zartha-Sossa, Jhon Wilder; Gafaro-Garcés, Delcy Camila; Melchor-Cahuana, Lourdes Gladys; Gonzalez-Tovar, Cristian (Frontiers in Sustainable Food Systems, 2022)
In the agroindustry, sieving is a unit operation of great value, this work aims to make a literature review on sieving in cereals, a search equation was carried out in the Scopus database with the keywords sieve, screen, food process, and cereal that resulted in 132 articles and 174 patents. Of the articles, 44 were directly related to sieving and 14 more had something to do with sieving; of the patents, in the last 10 years only 7 were directly related to sieving. To find new trends, raw materials, patent analysis, and information analysis, tables were built with name, year, author, keywords, countries, quartile, journal, relationship with the agroindustry, and purpose. Among the most important conclusions was the application of sieving in raw materials such as Rice, Corn, Wheat, Cotton, Millet, Quinoa, Almonds, Barley, Potato, Yucca, Microorganisms, Oats, Cotton, Protein, Peppers, and Chia Seed. Furthermore, the use of rotating and vibrating sieves was identified, and also their positive effects on the physicochemical, standardization, and classification of raw materials were identified. The different types of equipment or methods focused on sieving, that has been granted use or design patent, were also recognized.